Planning a dairy expansion - John F. Smith (Kansas Agricultural Experiment Station Research Reports, 1997)
Dairy farm size is increasing in all regions of the United States. In two of the largest dairy states, California and Wisconsin, mean herd sizes have increased 950% and 250%, respectively, since 1950. Dairy herds of 500 cows are common in all areas of the United States, and herds over 1,500 cows are common in the West producand Southeast. Many dairy operations are considering expansion of existing facilities or construction of new facilities to increase efficiencyor profitability. Before adding cows or facilities, dairy producers may want to answer the following questions: 1) How can I improve the efficiency of the present operation? 2) Can production per cow be increased? 3) Can the current herd be milked 3x per day? 4) Can I send the conheifers to a contract raiser and expand the cow herd? 5) What are my financial goals? 6) Where do I want to be in 5 and 10 years? 7) What are investthe expectations of other family members? 8)Do I have adequate acreage to expand the herd and manage the waste? 9) Do I want to manage employees? 10) Do I want to deal with regulatory agencies?; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Planning; Dairy; Expansion